A case study of electron precipitation fluxes due to plasmaspheric hiss. Issue 8 (7th August 2015) - Hardman, Rachael; Clilverd, Mark A.; Rodger, Craig J.; Brundell, James B.; Duthie, Roger; Holzworth, Robert H.; Mann, Ian R.; Milling, David K.; Macusova, Eva
Abstract We find that during a large geomagnetic storm in October 2011 the trapped fluxes of >30, >100, and >300 keV outer radiation belt electrons were enhanced at L = 3–4 during the storm main phase. A gradual decay of the trapped fluxes was observed over the following 5–7 days, even though no significant precipitation fluxes could be observed in the Polar Orbiting Environmental Satellite (POES) electron precipitation detectors. We use the Antarctic‐Arctic Radiation‐belt (Dynamic) Deposition–VLF Atmospheric Research Konsortium receiver network to investigate the characteristics of the electron precipitation throughout the storm period. Weak electron precipitation was observed on the dayside for 5–7 days, consistent with being driven by plasmaspheric hiss. Using a previously published plasmaspheric hiss‐induced electron energy e‐folding spectrum of E0 = 365 keV, the observed radio wave perturbation levels at L = 3–4 were found to be caused by >30 keV electron precipitation with flux ~100 el cm−2 s−1 sr−1. The low levels of precipitation explain the lack of response of the POES telescopes to the flux, because of the effect of the POES lower sensitivity limit and ability to measure weak diffusion‐driven precipitation. The detection of dayside, inner plasmasphere electron precipitation during the recovery phase of the storm is consistent with plasmaspheric hiss wave‐particle interactions and shows that the waves can be a significant influence on the evolution of the outer radiation belt trapped flux that resides inside the plasmapause.